A romance of two worlds - Corelli, Marie, 1855-1924 (Edinburgh University Press, 2019)
Marie Corelli's A Romance of Two Worlds is regarded as one of the most culturally important Victorian bestsellers. This critical edition offers instructive access to this multifaceted but still largely underappreciated novel.
Keywords: Christian life -- Fiction.; Mystics -- Fiction.; Teleportation -- Fiction.; Space and time -- Fiction.; English fiction -- Women authors -- 19th century.; Vie chrétienne -- Romans, nouvelles, etc.; Mystiques -- Romans, nouvelles, etc.; Télékinésie -- Romans, nouvelles, etc.; Christian life; English fiction -- Women authors; Mystics; Space and time; Teleportation; 1800-1899; Fiction